2016
DOI: 10.1158/2326-6066.cir-16-0177
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Regulation of Human MHC Class I Molecule Expression on Cancer Cells

Abstract: The major histocompatibility complex I (MHC-I) presents antigenic peptides to tumor-specific CD8+ T cells. The regulation of MHC-I by kinases is largely unstudied, even though many patients with cancer are receiving therapeutic kinase inhibitors. Regulators of cell surface HLA amounts were discovered using a pooled human kinome shRNA interference–based approach. Hits scoring highly were subsequently validated by additional RNAi and pharmacologic inhibitors. MAP2K1 (MEK), EGFR, and RET were validated as negativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
124
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 49 publications
8
124
2
Order By: Relevance
“…Most of the studies have shown that MEK inhibition can increase the expression of intrinsic and IFN-γ-induced HLA/ MHC I/II in cancer cell lines, including melanoma, mesothelioma, prostate, gastric, and esophageal cancer cell lines [103][104][105]. Similarly to BRAF inhibition, treatment of mutant melanoma cell lines with MEK inhibition enhances the expression of melanoma-differentiation antigens [92] and decreases the production of IL-10, IL-6, and VEGF [91].…”
Section: Mek Inhibitionmentioning
confidence: 99%
“…Most of the studies have shown that MEK inhibition can increase the expression of intrinsic and IFN-γ-induced HLA/ MHC I/II in cancer cell lines, including melanoma, mesothelioma, prostate, gastric, and esophageal cancer cell lines [103][104][105]. Similarly to BRAF inhibition, treatment of mutant melanoma cell lines with MEK inhibition enhances the expression of melanoma-differentiation antigens [92] and decreases the production of IL-10, IL-6, and VEGF [91].…”
Section: Mek Inhibitionmentioning
confidence: 99%
“…It will be important to discover pharmacological modulators of HLA-I that can be used for combination therapy with TCRm Abs or other HLA-I-based immunotherapies. For example, recent reports demonstrate that inhibition of MEK can increase cell-surface HLA-I, which may enhance TCRm Ab therapy (47). Additionally, several pharmacological agents that target histone-modifying enzymes, such as methytransferase inhibitors and histone deacetylase inhibitors, can induce expression of tumor-associated antigens, including PRAME, and lead to enhanced cytolysis by effector T cells (48)(49)(50).…”
Section: Control Peptides Used Were Established Hla-a2-binding Peptidmentioning
confidence: 99%
“…For instance, agents such as azacytidine and epidermal growth factor receptor inhibitors promote re-expression of tumor-associated antigens in malignant cells, 7 and radiotherapy induces expression of major histocompatibility complex class I molecules, 8 which are essential to the production of tumor-specific T cells. Because of the ample evidence showing that certain anticancer therapies increase the immunogenicity of tumor cells as part of their mechanism of action, this finding may reflect a negative impact of immunosuppression on the ability of the adaptive immune system to recognize and respond to neoantigens that become manifest during tumor progression or treatment.…”
mentioning
confidence: 99%